Impact of TNF-α Inhibitors on Body Weight and BMI: A Systematic Review and Meta-Analysis - Patsalos, Olivia; Dalton, Bethan; Leppanen, Jenni; Ibrahim, Mohammad A. A.; Himmerich, Hubertus (Frontiers in Pharmacology, 2020)
Objective: The aim of this systematic review and meta-analysis of longitudinal studies was to ascertain to effects of TNF- inhibitor therapy on body weight and BMI. Methods: Three databases (PubMed, OVID and EMBASE) were systematically searched from inception to August 2018. We identified prospective, retrospective and randomized controlled studies in adults with immune-mediated inflammatory diseases treated with TNF- inhibitors based on pre-specified inclusion criteria. A random-effects model was used to estimate standardised mean change (SMCC). Results: Twenty-six longitudinal studies with a total of 1245 participants were included in the meta-analysis. We found evidence for a small increase in body weight (SMCC = 0.24, p = .0006, 95% CI [0.10, 0.37]) and in BMI (SMCC = 0.26, p < .0001, 95% CI [0.13, 0.39]). On average, patients gained 0.90kg (SD = 5.13) under infliximab, 2.34kg (D = 5.65) under etanercept and 2.27kg (SD = 4.69) during treatment with adalimumab within the duration of the respective studies (4-104 weeks). Conclusion: Our results yield further support the for the view that TNF- inhibitors increase body weight and BMI as a potential side effect. Modulating cytokine signalling could be a future therapeutic mechanism to treat disorders associated with weight changes such as anorexia nervosa.